Further division of Alona Baird, 1843: separation and position of Coronatella Dybowski & Grochowski and Ovalona gen.n. (Crustacea: Cladocera) - van Damme, Kay; Dumont, Henri J. (Zootaxa, 2008)
We investigate morphology and taxonomic rank of several Alona species related to A. rectangula Sars, 1861. Despite high morphological intraspecific variability, a number of synapomorphies shows that taxa related to A. rectangula are sufficiently different in external and internal morphology from “true” Alona Baird, 1843. These are removed from Alona into separate genera. The rare West-African A. holdeni Green 1962 is redescribed and we describe a new species from North Africa, Arabia and islands in the Western Indian Ocean. We reinstate the name Coronatella Dybowski & Grochowski to receive A. rectangula, A. holdeni, and a new species, C. anemae. Sharing several synapomorphies, the subantarctic species A. weinecki Studer appears related to A. meridionalis Sinev, 2006. We assign them to Ovalona gen.n., similar in morphology to Coronatella, but with less limb reductions. At a higher level, we discuss morphology and distribution of both genera and of the similar A. elegans-group. To situate Coronatella within the subfamily, we introduce a “Coronatella-branch”, a group of medium-sized Aloninae with limb reductions, comprising Coronatella, Leberis, Celsinotum, A. dentifera, A. monacantha and possibly Karualona and A. verrucosa-group, in comparison with a “Hexalonabranch” and Alona s.str. Adaptations to life in temporary pools and salinity tolerance may have played an important role in separation and radiation of a Coronatella-branch.